The Role of Financial Management Behavior in Mediating The Relationship Between Financial Attitudes and Financial Literacy: Study of MSMEs Using E-Wallets in Pontianak City - Indonesia - Muhammad Zaini (AIBPM Publisher, 2022)
This study aims to examine the role of financial management behavior, and whether it can mediate the relationship between financial attitudes and financial literacy. The independent variable in this study is financial attitudes, the dependent variable is financial literacy and the mediating variable is financial management behavior. This study uses a quantitative design with the WarpPLS analysis tool. The data collection method used by distributing questionnaires with the Likert scale, this study had a total of 200 respondents who managed MSMEs in Pontianak City. The results of this study are financial attitudes have a significant influence on financial management behavior, and financial management behavior can mediate the relationship between financial attitudes and financial literacy of MSMEs in Pontianak City. Appropriate financial management behavior will have an impact on the ability of MSMEs to manage their finances. So that, with the application of the right financial attitude, the increase in knowledge about financial literacy will be better.